Monitoramento em tempo real da morfologia na extrusão da blenda polimérica polipropileno/ nylon 6 - Pinheiro, Luís Antonio (Universidade Federal de São Carlos, 2006)
The aim of this work is to assess in real time the morphological parameters of polypropylene and polyamide 6 blends during the extrusion process. An optical detector based on the visible light transmitted and extinction principle was assembled in a slit die located at the exit of a twin screw extruder in order to get the changes in the polyamide 6 particle concentration and size. The influence of particle size and concentration was first verified during bench calibration, where it was observed that the light extinction was greater the higher the concentration and the lower the particle size. In the case of mixtures an additional relation concerned to changes in size and density was verified. It was also stated that the detector records the ponderal average size of a set of particles. During extrusion experiments, the analyses were performed in the steady and transient state. In both cases it was verified that normalized signal intensity increases with increasing particle concentration and decreasing the dispersed phase size. Infrared analysis and images obtained from scanning electron microscopy confirmed these results. The correlation between dispersed phase concentration and size with the detector s normalized signal was established through the elaboration of regression equations. The plot of normalized signal as a function of the dispersed phase concentration and size enabled the calculation of the extinction cross section values for the PP/ PA6 blend.
Real time monitoring of morphology on extrusion of the polypropylene/ nylon 6 polymeric blend
Keywords: Polímeros; Processo de extrusão; Blendas poliméricas; Morfologia; Calibração; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS